2016
DOI: 10.1016/j.schres.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavior Therapy for psychosis based Guided Self-help (CBTp-GSH) delivered by frontline mental health professionals: Results of a feasibility study

Abstract: Availability of Cognitive Behavior Therapy for psychosis (CBTp) is limited in spite of strong evidence base. The purpose of this study was to determine the feasibility of a CBTp based Guided Self-help (CBTp-GSH) in comparison to Treatment As Usual (TAU). The secondary outcomes were a reduction of symptoms of schizophrenia using Positive and Negative Symptom Scale (PANSS) & Disability (WHO DAS 2.0). A total of 33 adults with a DSM-IV diagnosis of schizophrenia was recruited from community mental health services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…Examination of supplementary figure 3 suggested that the trial by Habib et al 47 was a significant outlier because its 95% CI did not overlap with that of the pooled effect size. The effect from one RCT by Naeem et al 49 was also identified as a potential outlier. We therefore assessed heterogeneity when excluding both outliers in an exploratory sensitivity analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examination of supplementary figure 3 suggested that the trial by Habib et al 47 was a significant outlier because its 95% CI did not overlap with that of the pooled effect size. The effect from one RCT by Naeem et al 49 was also identified as a potential outlier. We therefore assessed heterogeneity when excluding both outliers in an exploratory sensitivity analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Post hoc investigation established that heterogeneity introduced to the hallucinations comparisons was largely attributable to 2 outliers, one of which adapted CBTp for application in other cultural settings, 47 while the other applied group-based self-help CBTp. 49 Similarly, another RCT of culturally adapted CBTp contributed to heterogeneity in the delusions comparisons. 58 Our earlier review conceptualized case formulation–driven CBTp RCTs as “apples” in comparison to “oranges”; a broader and more inclusive sample of RCTs applying CBTp principles in alternative style.…”
Section: Discussionmentioning
confidence: 99%
“…Naeem et al [ 32 ] contests that self-guided CBT (SG-CBT) can be used as an intervention with minimum direct contact. For patients in need of CBT who face obstacles hindering face-to-face attendance, a self-guided platform to access therapy holds many advantages.…”
Section: Introductionmentioning
confidence: 99%
“…62 Web-based interventions are yet another alternative to enhance patients' access to CBT for schizophrenia and there is evidence regarding its feasibility and preliminary efficacy. 63 More recently, Naeem et al 64 developed a feasibility study protocol using a self-guided CBT program: this is an intervention which is predominately designed to be conducted without contact with health professionals and which could provide a cheap, flexible and easy tool for CBT implementation. Although their sample included mainly patients with moderate symptomatology and low disability levels, the authors reported a high retention rate and acceptability as well as improved scores regarding disability and positive, negative and general psychopathology.…”
Section: ■ Results and Discussionmentioning
confidence: 99%